Genetic Assessment of Moroccan Tomato (Solanum lycopersicum L.) Genotypes by RAPD and SSR Markers (Atlas Journal of Biology, 2017)
For the first time eight local tomato cultivars collected from four different regions of Morocco were assessed with RAPD and SSR methods. Most of RAPD markers give monomorphic banding profiles. Only OPU03 marker showed a total of 4 polymorphic amplicons out of 8 recorded in FIGUIG2 cultivar. The analysis with SSR markers gives more polymorphism. The number of alleles amplified assessed from 2 to 5 alleles among cultivars. The similarity matrix subjected by the unweighted pairgroup arithmetic method (UPGMA) clustering grouped the cultivars in four groups where FIGUIG2 cultivar formed a separate and more distant cluster. In addition this cultivar holds the very high percentage of uniformity (99%) indicating that is an homogeneous traditional cultivar with high purity. This genotype can be conserved and used in breeding programs. More traditional Moroccan cultivars must be collected in order to determine their genetic structure.